Innovative sport technology through cross-disciplinary research: Future of sport science - Ellapen, T. J.; Paul, Y. (South African Journal for Research in Sport, Physical Education and Recreation, 2016)
This paper provides an overview of the advantages and disadvantages of innovative sport technology brought about by cross-disciplinary research in sport, engineering, medical and material sciences. Sport technology has subsequently contributed greatly to the enhancement of epidemiology, prevention and management of injuries, management of non-communicable diseases, physical activity and sport performance. The debate raging between sport scientists and academics pertaining to the greater amount of attention paid to sport technology and cross-disciplinary research in sport and the diminished quality and quantity of subject matter is highlighted. The paper also raises the following ethical question: Should only affluent elite athletes have the opportunity to capitalise on this technology? Is this jeopardising the success of less affluent athletes?